A Short Note on the Net Stable Funding Ratio Requirement with Endogenous Money. (17th August 2016) - Kauko, Karlo
Abstract : The Net Stable Funding Ratio (NSFR) regulation stipulates that banks' available stable funding shall be at least equal to the required stable funding. This should reduce banks' liquidity risks. In the current monetary system, deposit money is created by lending, but the NSFR requirement restricts the possibilities to grant loans, limiting the availability of stable funding. In a closed economy, this contradiction poses no macroeconomic problems. However, the outcome may be unstable if there is a substantial amount of foreign debt financed via the international interbank market; a minor shock can have a drastic impact on loan and deposit stocks.